Best Practice for Creating Dynamic Network Models based on Power Flow Models for DSA Applications - Porst, Johannis; Burlakin, Ilya; Scheiner, Elisabeth; Luther, Matthias; Samaan, Stefanie; Knittel, Markus; Momeni, Mojtaba; Moser, Albert; Just, Hendrik; Horn, Stefan (17. Symposium Energieinnovation, 2022)
This paper presents the development process of dynamic network models based on power flow data of Continental Europe. Typical power flow modeling issues and feasible solutions are shown and controller models for multiple grid components are designed. For validation, a network model in DIgSILENT PowerFactory is compared to one in MatPAT, both being subject to the described development proces
Keywords: Power System Stability Studies; Standard Dynamic Models; Transient stability

Dynamic Modelling of Transmission Systems Based on Primary Energy Sources - Burlakin, Ilya; Porst, Johannis; Scheiner, Elisabeth; Kuri, Ananya; Mehlmann, Gert; Kühnapfel, Uwe; Luther, Matthias (Conference on Sustainable Energy Supply and Energy Storage Systems, 2022)

Impact of Inverter-Based Generation on Voltage Stability in a Modified Nordic Test System - Heusinger, Elisabeth; Porst, Johannis; Raab, Alexander; Luther, Matthias; Samaan, Stefanie (2021 IEEE Kansas Power and Energy Conference (KPEC), 2021)

Impact of Time Constants of Reactive Power Sources on Short-Term Voltage Stability - Scheiner, Elisabeth; Burlakin, Ilya; Strunz, Niklas; Raab, Alexander; Mehlmann, Gert; Luther, Matthias (2022 IEEE Transportation Electrification Conference and Expo (ITEC), 2022)
As a result of the enduring change in power systems the risk of blackouts caused by voltage instability is growing. This paper addresses the challenges of future requirements and Var equipment. The focus is on enhancing the short-term dynamic performance of future electrical power systems. In contrast to traditional steady-state considerations, possible placement options of reactive power sources using dynamic stability indicators based on voltage trajectories are determined. After identifying worst-case fault scenarios based on the Contingency Severity Index (CSI), different time constants for the reactive power control of MSC and STATCOM and their effects on the short-term voltage stability are investigated. The preselection is used to reduce the computational effort and is based on indicators that are determined using RMS calculations. The approach is tested using a modified Nordic Test System with a 35% share of renewable energy source
Keywords: dynamic reactive power compensation; dynamic security; MSC; short-term voltage stability; STATCOM

Low-power contactless LC-tank based respiratory sensor - Scheiner, Benedict; Schellenberger, Sven; Shi, Kilin; Heusinger, Elisabeth; Michler, Fabian; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (Electronics Letters, 2019)

Setpoint Adaption of DC Converters Integrated in AC Systems using Security Constrained Optimal Power Flow - Heusinger, Elisabeth; Raab, Alexander (Bd. 77, 2019)